TANGGAPAN MASYARAKAT DESA WONOREJO KECAMATAN MANGKUTANA KABUPATEN LUWU TIMUR TERHADAP DAKWAHTAINMENT ISLAM ITU INDAH DI TRANS TV - Audah Mannan; Fatmawati Fatmawati (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2019)
The main issues of this research are 1) Community responses from Wonorejo Village, Mangkutana Subdistrict, East Luwu Regency to Da'wahtainment Islam itu Indah on Trans TV 2) Factors that encourage the public to watch the Islamic Da'wahwah program that is Beautiful on Trans TV. The results of this study are; Demonstrating responses The people of Wonorejo Village are more interested in propaganda material that is 'akhlakul karimah' with a light and simple material delivery. Because, the material is more often found in everyday life. Factors that encourage the public to witness Islam itu Indah’s propaganda programs on Trans TV are the delivery of interesting and easily understood propaganda material, the theme presented is very interesting to the viewer, the desires and needs of the community towards propaganda are very complex with themes related to daily life. That is akhlakul karimah.